2012
DOI: 10.1080/15320383.2012.664184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sludge and pH Adjustment on Cd Speciation in Soil and Growth and Cd Accumulation in Pak Choi

Abstract: The objective of this study was to assess the effects of soil pH adjustment and treatment with sludge on plant growth and cadmium (Cd) accumulation in Chinese cabbage (pak choi) grown in Cd-contaminated soils. Soil was artificially spiked to raise its final Cd concentration to 10 mg/kg, adjusted to different pH values, and then supplemented with 5% sludge: either biosolids (BS) from wastewater treatment or sludge from drinking water treatment (WTS). Pak choi seeds were sown and the seedlings potted in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Relative to control without applying BS, the Cd concentrations in the edible parts of pak choi grown in the Cd-contaminated soils amended with BS also increased (Lu et al 2012). Experimental results of forgoing studies show that BS can promote both the biomass and the accumulation of Cd which may decline the period needed in phytoextraction.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Relative to control without applying BS, the Cd concentrations in the edible parts of pak choi grown in the Cd-contaminated soils amended with BS also increased (Lu et al 2012). Experimental results of forgoing studies show that BS can promote both the biomass and the accumulation of Cd which may decline the period needed in phytoextraction.…”
Section: Introductionmentioning
confidence: 91%
“…According to US Environmental Protection Agency in 40 CFR Part 503, biosolids (BS) are defined as sewage sludge that is beneficially reused (US EPA 2000) and could raise the dry weight (DW) of soybeans (Vieira 2001) and pak choi (Lu et al 2012). Relative to control without applying BS, the Cd concentrations in the edible parts of pak choi grown in the Cd-contaminated soils amended with BS also increased (Lu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that pH greatly affects the bioavailability of Cd, such that the effectiveness of Cd in the soil is higher when the pH is lower, thus intensifying its damage to crops [58,59]. Natural illite contains many alkaline earth metals, such as potassium.…”
Section: Stabilization Mechanismmentioning
confidence: 99%